Erythrocyte oxidative stress markers in children with sickle cell disease - Priscila Bacarin Hermann; Mara Albonei Dudeque Pianovski; Railson Henneberg; Aguinaldo José Nascimento; Maria Suely Soares Leonart (Elsevier, 2016)
Objective: To determine eight parameters of oxidative stress markers in erythrocytes from children with sickle cell disease and compare with the same parameters in erythrocytes from healthy children, since oxidative stress plays an important role in the pathophysiology of sickle cell disease and because this disease is a serious public health problem in many countries. Methods: Blood samples were obtained from 45 children with sickle cell disease (21 males and 24 females with a mean age of 9 years; range: 3-13 years) and 280 blood samples were obtained from children without hemoglobinopathies (137 males and 143 females with a mean age of 10 years; range: 8-11 years), as a control group. All blood samples were analyzed for methemoglobin, reduced glutathione, thiobarbituric acid reactive substances, percentage of hemolysis, reactive oxygen species, and activity of the enzymes glucose 6-phosphate dehydrogenase, superoxide dismutase, and catalase. Data were analyzed using Student's t-test and were expressed as the mean ± standard deviation. A p-value of <0.05 was considered significant. Results: Significant differences were observed between children with sickle cell disease and the control group for the parameters methemoglobin, thiobarbituric acid reactive substances, hemolysis, glucose 6-phosphate dehydrogenase activity, and reactive oxygen species, with higher levels in the patients than in the controls. Conclusions: Oxidative stress parameters in children's erythrocytes were determined using simple laboratory methods with small volumes of blood; these biomarkers can be useful to evaluate disease progression and outcomes in patients. Resumo: Objetivo: Determinar parâmetros de estresse oxidativo em eritrócitos de crianças com doença falciforme e compará-los com os mesmos parâmetros em eritrócitos de crianças saudáveis, pois o estresse oxidativo desempenha um importante papel na fisiopatologia da doença falciforme, considerada um sério problema de saúde pública em muitos países. Métodos: Foram obtidas amostras de sangue de 45 crianças com doença falciforme (21 meninos e 24 meninas com média de 9 anos, variação de 3 a 13 anos) e 280 amostras de sangue de crianças sem hemoglobinopatias (137 meninos e 143 meninas com média de 10 anos, variação de 8 a 11 anos), como grupo controle. Em todas as amostras foram determinados meta-hemoglobina, glutationa reduzida, substâncias reativas ao ácido tiobarbitúrico, porcentagem de hemólise, espécies reativas de oxigênio e atividade das enzimas glucose6-fosfato desidrogenase, superóxido dismutase e catalase. Os dados foram analisados com o teste t de Student e foram expressos como média ± desvio padrão. Um valor de p < 0,05 foi considerado significativo. Resultados: Foram observadas diferenças significativas entre as crianças com doença falciforme e o grupo controle para os parâmetros meta-hemoglobina, substâncias reativas ao ácido tiobarbitúrico, porcentagem de hemólise, espécies reativas de oxigênio e atividade da enzima glucose6-fosfato desidrogenase, com níveis aumentados nos pacientes. Conclusões: Foi possível determinar parâmetros de estresse oxidativo em eritrócitos de crianças, com técnicas laboratoriais simples e pequenos volumes de sangue. Esses biomarcadores podem ser úteis na avaliação da progressão e dos resultados de tratamentos da doença. Keywords: Oxidative stress, Sickle cell disease, Children, Palavras-chave: Estresse oxidativo, Doença falciforme, Crianças